Caregiver Reported Oral Health-Related Quality of Life in Young American Indian Children - Braun, Patricia A. (2014)
BACKGROUND: American Indian/Alaska Native (AI/AN) children experience high rates of dental decay, yet their pediatric oral health-related quality of life (POQL) has not been described. METHODS: We measured POQL in AI children and compared it in children with reported excellent/very good/good versus fair/poor oral health status (OHS) and assessed association of OHS, child’s age, dental service utilization, and dental insurance on POQL scores. RESULTS: Caregivers of 143 AI (100%), young (mean age 25.1 months) children reported their POQL score as 4.2 (scale 0–100, lower score indicates better POQL); OHS as excellent (35%), very good (27%), good (21%), fair (14%), and poor (3%); and utilization of urgent dental services (12%). Worse POQL was associated with worse OHS (p = 0.01). After adjustment, worse POQL was associated with increased reported use of urgent dental services (p=0.004). CONCLUSIONS: POQL of young AI children was generally favorable but worsened with increased utilization of urgent dental services.